Surveillance of Nipah virus in Pteropus medius of Kerala state, India, 2023 - Balasubramanian, R.; Mohandas, Sreelekshmy; Thankappan, Ullas P.; Shete, Anita; Patil, Dilip; Sabarinath, Kannan; Mathapati, Basavaraj; Sahay, Rima; Patil, Deepak; Yadav, Pragya D. (Frontiers in Microbiology, 2024)
Introduction Since 2018, the Indian state of Kerala has reported four Nipah virus (NiV) disease outbreaks, raising concerns about NiV spillover from bats to the human population. Considering this, a cross-sectional study was undertaken in the Pteropus medius bat population around the Nipah virus-affected regions of Kozhikode, Kerala, India, during February, July, and September 2023. Methods Throat swabs, rectal swabs, and organ samples were collected from bats to test for NiV using the real-time reverse transcriptase polymerase chain reaction (RT-PCR), while serum samples were screened for anti-Nipah IgG antibodies through ELISA. Results An overall seroprevalence of 20.9% was observed in 272 P. medius bats tested. The throat and rectal swab samples of 321 bats were negative for NiV RNA. However, 4 of 44 P. medius bats tested positive for NiV in their liver/spleen samples. The partial N gene retrieved showed more than 99% similarity with the earlier reported NiV genome from Kerala state, India. Discussion The findings of the study caution that there is a spillover risk in the region and necessary precautions should be taken.